The power of denial : Buddhism, purity, and gender - Faure, Bernard (Buddhisms., 2003)
Innumerable studies have appeared in recent decades about practically every aspect of women's lives in Western societies. The few such works on Buddhism have been quite limited in scope. In The Power of Denial, Bernard Faure takes an important step toward redressing this situation by boldly asking: does Buddhism offer women liberation or limitation? Continuing the innovative exploration of sexuality in Buddhism he began in The Red Thread, here he moves from his earlier focus on male monastic sexuality to Buddhist conceptions of women and constructions of gender. Faure argues that Buddhism is n.